PB13. Is 0.9 Hz rTMS-induced LTD-like corticospinal plasticity dependent on μ-rhythm phase during the intervention?. Issue 8 (August 2018) - Baur, D.; Zrenner, C.; Vasilkovska, T.; Ziemann, U.
Abstract : Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive method to stimulate the human brain. It is capable of inducing plasticity and altering the state of the brain. The method is widely used by clinicians and neuroscientists alike and has increasing experimental, diagnostic and therapeutic applications. Yet so far, it often suffers from a considerable variability and low effect size. Low-frequency rTMS of the primary motor cortex at near 1 Hz (0.9 Hz) induced long-term depression (LTD)-like effects on corticospinal excitability (Chen et al., 1997). It was recently demonstrated that corticospinal excitability as well as induction of long-term potentiation (LTP)-like plasticity effects depend on the phase of the 8–12 Hz alpha oscillation of the somatosensory cortex ( μ -alpha oscillation) at the time of stimulation. LTP-like corticospinal plasticity resulted from real-time EEG-triggered 100 Hz burst rTMS during the negative but not positive peak of the μ -alpha oscillation (Zrenner et al., under revision). Since LTD-like plasticity of near 1 Hz rTMS was examined in random phase ('open loop') rTMS protocols only so far, it is unknown, whether the observed effect is dependent on a phase of the μ -alpha oscillation and by which phase it might be controlled. Here we address this question using a real-time EEG-triggered TMS set-up. Motor evoked potentials (MEPs) are recorded from right hand muscles before and after a phase-triggered 15-min 0.9 Hz rTMS intervention in a double-blind randomized cross-over design: Each subject will undergo three phase conditions in the 0.9 Hz intervention: (1) random phase stimulation, (2) stimulation triggered by the EEG positive peak and (3) stimulation triggered by the negative peak of the ongoing μ -rhythm. The results of this study will show whether μ -oscillation phase modules LTD-like corticospinal excitability induced by rTMS near 1 Hz. They will have substantial implications for understanding the neurophysiology underlying plasticity induction and for the development of personalized EEG-triggered stimulation protocols. The project is currently ongoing. The results will be presented at the conference.